MRI-based simulation of treatment plans for ion radiotherapy in the brain region - Rank, Christopher M.; Hünemohr, Nora; Nagel, Armin Michael; Röthke, Matthias C.; Jäkel, Oliver; Greilich, Steffen (Radiotherapy and oncology, 2013)
Purpose - To test the potential of MRI-based treatment plan simulation for ion radiotherapy in the brain region. - Materials and methods - A classification-based tissue segmentation method based on discriminant analysis was employed to derive so-called pseudo CT numbers from MR images of three patients with lesions in the head region undergoing ion radiotherapy. Treatment plans for ions, and for comparison purposes also for photons, were subsequently optimized and simulated using both MRI-based pseudo CT and a standard X-ray-based reference CT. - Results - Pseudo CTs revealed mean absolute errors in CT number in the range of 141-165HU. While soft tissue was in good agreement with reference CT values, large deviations appeared at air cavities and bones as well as at interfaces of different tissue types. In simulations of ion treatment plans, pseudo CT optimizations showed small underdosages of target volumes with deviations in the PTV mean dose of 0.4-2.0% in comparison to reference CT optimizations. In contrast, the PTV mean dose in photon treatment plans differed by no more than 0.2%. - Conclusions - The main challenge in deriving pseudo CT numbers from MRI was the correct assignment of air and compact bone. In this study, the impact of deviations on simulations of ion and photon treatment plans in the brain region was small, however for more complicated morphologies a further improvement of the classification method including MR imaging of compact bone is required.